1978
DOI: 10.1152/ajprenal.1978.235.3.f246
|View full text |Cite
|
Sign up to set email alerts
|

Distribution along the rat nephron of three enzymes of gluconeogenesis in acidosis and starvation

Abstract: Methods were devised or modified which made it possible to measure phosphoenolpyruvate carboxykinase, fructose-1,6-bisphosphatase, and glucose-6-phosphatase in seven defined parts of single nephrons and in patches from thin limb and papilla areas dissected from freeze-dried microtome sections of rat kidney. All three enzymes were essentially confined to the proximal tubule. In normal kidneys, the levels were highest in the proximal convoluted tubule. Glucose-6-phosphatase was 20 times higher in the early part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
2

Year Published

1979
1979
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 0 publications
5
63
0
2
Order By: Relevance
“…Moreover, renal cells which have appreciable glucose phosphorylating capacity and thus the ability to accumulate glycogen have relatively little glucose 6-phosphatase activity, whereas cells having little phosphorylating capacity possess abundant activity of glucose 6-phosphatase and other gluconeogenic enzymes [28,34]. It is thus likely that release of glucose by the normal kidney is due mainly if not exclusively to gluconeogenesis.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Moreover, renal cells which have appreciable glucose phosphorylating capacity and thus the ability to accumulate glycogen have relatively little glucose 6-phosphatase activity, whereas cells having little phosphorylating capacity possess abundant activity of glucose 6-phosphatase and other gluconeogenic enzymes [28,34]. It is thus likely that release of glucose by the normal kidney is due mainly if not exclusively to gluconeogenesis.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Several key enzymes and proteins involved in ammoniagenesis and gluconeogenesis are specifically induced in the proximal tubule cells during acidosis (3,30). This includes the activities of PAG, GDH, and phosphoenolpyruvate carboxykinase (4,31).…”
Section: Sn1 Is Induced In Cortical Tubule Cells During Chronic Metabmentioning
confidence: 99%
“…These changes in tubule function are associated with changes in the activities of a number of proteins, including the apical membrane Na ϩ /H ϩ antiporter (7), glutaminase and glutamate dehydrogenase (8), and phosphoenolpyruvate carboxykinase (9), which may affect intracellular substrate availability for protein turnover, amino acid metabolism and/or transport, and gluconeogenesis. It has been shown that in tubule epithelial cells, the associated increase in ammonia production, rather than the acidosis per se, is responsible for favoring tubular hypertrophy (10 -12).…”
mentioning
confidence: 99%